Characteristic differences in barrier and hygroscopic properties between normal and cosmetic dry skin. I. Enhanced barrier analysis with sequential tape-stripping - Lu, N.; Chandar, P.; Tempesta, D.; Vincent, C.; Bajor, J.; McGuiness, H. (International journal of cosmetic science, 2014)
Synopsis Objective Cosmetic dry skin often has a lower hydration level but a similar apparent barrier function, as measured by transepidermal water loss (TEWL), than that of the normal skin. To investigate the intrinsic difference in barrier property and moisture‐holding ability between the cosmetic dry and normal skin, we developed a new clinical and data analysis procedure based on sequential tape‐stripping with TEWL measurement, coupled with chemical analysis for protein and natural moisturizing factors (NMF) in the stratum corneum. Methods A clinical study consisting of 64 healthy Caucasian female subjects with normal and cosmetic dry skin was conducted according to our clinical and data collection protocols. After the baseline visual dryness assessment, 20 tape‐strips were placed and removed on each test site using D‐Squame tapes. TEWL was measured at baseline and after the 5th, 10th, 15th and 20th tape‐strips. All tapes were analysed for protein mass via chemical extraction and the Pierce BCA protein assay, as well as using an infrared densitometry device SquameScan 850A. The stratum corneum thickness and barrier quality (water transport resistance per thickness of the stratum corneum) were decoupled from the apparent barrier function using the TEWL and protein data. Results A linear relationship between 1/TEWL and cumulative protein removal was observed for both normal and cosmetic dry skin. However, the slope of the linear relation was significantly steeper for normal skin, and significantly more protein was removed from cosmetic dry skin. The results showed that on average, the barrier quality of the stratum corneum of the normal skin is about 40% higher than that of the dry skin, whereas the stratum corneum of the dry skin is about 30% thicker than that of the normal skin. In addition, the amount of SC removal in sequential tape‐stripping is generally non‐uniform. Conclusion Our results demonstrated that there are characteristic differences in the barrier property between normal and cosmetic dry skin. In comparison to the normal skin, the stratum corneum of the cosmetic dry skin is considerably thicker, however, with a lower barrier quality. The results also showed that the amount of the SC removal in sequential tape‐stripping is generally non‐uniform. Therefore, the number of tape strips is not a good indicator for the tape‐stripping depth. Résumé Objectif La peau sèche (selon les critère cosmétiques) a souvent un niveau d'hydratation plus faible, mais une fonction barrière apparente similaire, telle que mesurée par la perte insensible en eau (PIE), à celle de la peau normale. Pour étudier la différence intrinsèque entre la propriété de barrière et la capacité de rétention d'eau entre la peau sèche et la peau normale, nous avons développé une nouvelle procédure clinique et d'analyse des données sur la base séquentielle d'arrachement d'adhésifs (‘tape‐stripping) avec mesure de la PIE, couplée à l'analyse chimique des protéine et des facteurs d'hydratation naturels (NMF) dans le stratum corneum. Méthodes L' épaisseur de la couche cornée et de la qualité de la barrière (résistance au transport de l'eau par l'épaisseur de la couche cornée) sont découplés de la fonction de barrière apparente. Une étude clinique comprenant 64 sujets féminins sains de type caucasien avec la peau normale et la peau sèche a été effectuée selon nos protocoles cliniques et de collecte de données. Après l' évaluation de base de la sécheresse visuelle, 20 bandes D‐Squame ont été placés et retirés sur chaque site d'essai. Deux mesures séquentielles de PIE ont été prises pour assurer un état stable a été prise après la bande ‐froid. La quantité de protéine sur des bandes D‐ Squame a été analysée en utilisant un appareil de densitométrie infrarouge SquameScan 850A. Toutes les bandes ont également été analysés pour la teneur en protéine par analyse chimique. Résultats Une relation linéaire entre 1/TEWL et l'enlèvement cumulatif de protéine a été observée pour la plupart des sujets individuels dans cette étude, indépendamment de leurs qualités de sécheresse visuels. En accord avec la conclusion par Kali et al. nos résultats indiquent que malgré le caractère moléculaire hétérogène du SC, la résistance de transport de l'eau à travers le SC semble être homogène. En outre, la même conclusion vaut non seulement pour les peaux normales, mais aussi pour les peaux sèches. Les résultats montrent que, en moyenne, la qualité de la fonction barrière de la couche cornée de la peau normale est d'environ 40% supérieure à celle de la peau sèche, tandis que la couche cornée de la peau sèche est d'environ 30% plus épaisse que celle de la peau normale. Conclusion Les résultats présentés ici et dans les études précédentes ont montré clairement que la quantité du SC arrachée séquentiellement est de type non ‐ uniforme. L'analyse s'appuyant sur des chiffres du tape‐stripping peut conduire à des erreurs importantes et même à des conclusions abusives et devrait donc être évitée. Clinical results showed that the stratum corneum of the cosmetic dry skin was considerably thicker than that of the normal skin; however, the barrier quality of the dry skin was intrinsically lower. The difference in barrier properties between cosmetic dry and normal skin was evident in the plot of 1/TEWL vs. cumulative protein removal by tape‐stripping.